Life on the Andes and chronic mountain sickness - Monge M., Carlos (1942)
Since prehistoric time, human life flourished in the high plateaus of South America (at 185 mm. of pressure ). The author states the general, as well as the particular differences between the inhabitants of the coast (who always live at sea level), and those newly arrived to high altitudes, as well as those completely acclimated there. He briefly reviews his own work on the subject, and that of other Peruvian and foreign authors. He concludes that the Andean man, has all the characteristics of an athlete, and much of the qualities we require of a pilot especially one who files in high altitudes. Acclimated people and animals are 100 % reproductive where as new corners are occasionally sterile. From the human and industrial standpoint this fact is of the greatest significance. The characteristic biological qualities of the acclimatized man, influence to the highest degree his social behavior. The author cites historic sources which bear on this point of view. He discusses a special climatic-physiologic variety of human race. Concerning Chronic Mountain Sickness, the author is convinced that it is due to loss of acclimatization. A man who climbs to high altitudes, sometimes suffers from a lack of ability to adapt himself, in which various transition forms are noticeable: that is : Acute, Sub acute and Chronic Mountain Sickness, Adaptation is a malady. The cure, is of course, acclimatization. When acclimatization does not occur, we have Chronic Mountain Sickness. This is also found among native population, when in isolated cases, they lose their acclimatization. Their symptoms correspond to those of Vaquez-Osler disease. The author describes certain forms of hematic, respiratory, circulatory, and nervous predominance, all of which he analyzes. The cases mentioned, recover when the patient descends to lower altitudes or to sea level. The question discussed is a climatic pathologic variety of a disease found in man, as well as in animals.